Characteristics of Metacarpal Fracture Patients in Orthopaedic and Traumatology Department of Dr. Mohammad Hoesin General Hospital Period January 2017 - December 2019 - Daniel Ferrand; Nur Rachmat Lubis (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2021)
Introduction: Metacarpal fracture is the most common injury of manus region found in the emergency department (ER). Injuries to the manus region, especially metacarpal fractures, can cause great losses, especially in the productive age range. The diagnostic accuracy of metacarpal fractures is required for further operative or nonoperative management as indicated. Methods: This research is a retrospective study with a descriptive design. The aim of this study was to describe patient characteristics based on age, gender, fracture position, fracture location, mechanism of injury, and metacarpal fracture management. There are 48 cases in this study. Results: The metacarpal fracture patients dominated by male. Most common found in 20-29 years age. The youngest age was 5 years and the oldest was 60 years (mean age 31.06 Â± 14.23 years). Most fracture position found on the right side of the fifth metacarpal location. Mechanism of injur dominated by low energy trauma (LET). Open reduction management with miniplate-type dominant in this study sample. Conclusion: Early prevention and treatment of orthopedic surgery can be considered as the most important for the management of metacarpal fracture patients.